2021
DOI: 10.1002/art.41623
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Bone Mineral Density and Autoantibodies in Patients With Rheumatoid Arthritis

Abstract: Objective. Autoantibodies, such as anti-citrullinated protein antibodies (ACPAs), have been described as inducing bone loss in rheumatoid arthritis (RA), which can also be reflected by bone mineral density (BMD). We therefore examined the association between osteoporosis and autoantibodies in two independent RA cohorts.Methods. Dual x-ray absorptiometry (DXA) of the lumbar spine and left hip was performed in 408 Dutch patients with early RA during 5 years of follow-up and in 198 Swedish patients with early RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
6
17
1
Order By: Relevance
“…Studies of inception cohorts of patients with RA in Sweden demonstrated an association between ACPA and disease activity over time among those diagnosed in 1996-1999, but not in those diagnosed in 2006-2009 (116). Furthermore, whereas earlier studies reported a more pronounced general loss of bone mass in seropositive RA (117,118), more recent inception cohort studies did not demonstrate any difference in change of bone mineral density over time in ACPA positive compared to ACPA negative RA (119).…”
Section: Autoantibodies In Diagnosis and Prognosis Of Racontrasting
confidence: 65%
“…Studies of inception cohorts of patients with RA in Sweden demonstrated an association between ACPA and disease activity over time among those diagnosed in 1996-1999, but not in those diagnosed in 2006-2009 (116). Furthermore, whereas earlier studies reported a more pronounced general loss of bone mass in seropositive RA (117,118), more recent inception cohort studies did not demonstrate any difference in change of bone mineral density over time in ACPA positive compared to ACPA negative RA (119).…”
Section: Autoantibodies In Diagnosis and Prognosis Of Racontrasting
confidence: 65%
“…The effects of early and intensive management on the epidemiology of OP in recent-onset RA remain poorly defined. Few studies have reported substantial stability of BMD in modern early RA populations (19,(32)(33)(34)(35), with the highest rates of bone loss being observed at the hip in the first two years after treatment start (35), especially in patients receiving glucocorticoids (36). Although the exact rates of BMD variations are not comparable across studies due to different demographic characteristics, anti-rheumatic treatments and use of prophylactic measures, our results confirm that early RA patients collectively undergo only minor changes in systemic BMD upon tightly controlled management.…”
Section: Discussionmentioning
confidence: 99%
“…Our results however do not implicitly assign a prominent role to ACPA, and we are aware that a number of important RA-related and non-related factors, such as disease activity, type of medications and duration of follow-up might mitigate or even contrast the association between autoantibodies and early bone loss found here. Accordingly, Amkreutz et al (19) recently failed to demonstrate significant relationships between ACPA and variations in BMD during five and ten years from treatment start in two independent populations of early RA and undifferentiated arthritis. However, also in this study, some possible differences seemed to arise, with the Swedish ACPA-positive sub-cohort showing a trend for reduced BMD at both the spine and the hip during the first two years, followed by further relative stabilization or even increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations